Investigation of Cryptosporidium spp. and Enterocytozoon bieneusi in free-ranged livestock on the southeastern Qinghai–Xizang Plateau, China - Xiaoxue Peng; Xu Wang; Jinhua Jian; Qingqiu Zuo; Hua Liu; Yaxue Wang; Yaxin Su; Jianping Cao; Bin Jiang; Yujuan Shen (BMC Infectious Diseases)
Abstract Background Cryptosporidium spp. and Enterocytozoon bieneusi are zoonotic pathogens with global distribution, infecting humans and various livestock. For yaks, Tibetan sheep and horses, the traditional grazing models still hold a main position. After these animals become infected, it not only hinders the development of animal husbandry but also increases the risk of Cryptosporidium spp. and E. bieneusi transmission between livestock and herdsmen. Methods In the present study, a total of 750 fecal samples were collected from yaks, Tibetan sheep and horses in Shiqu County, Sichuan Province, from July to August 2023, and were analyzed by nested Polymerase chain reaction (PCR) amplification of the small subunit ribosomal RNA (SSU rRNA) gene of Cryptosporidium spp. and internal transcribed spacer (ITS) gene of E. bieneusi. Results The prevalence of Cryptosporidium spp., and E. bieneusi were 2.1% (16/750) and 1.5% (11/750), respectively. Mixed infections of Cryptosporidium spp. and E. bieneusi were detected in two samples. Among these positive fecal samples, one Cryptosporidium species (Cryptosporidium suis) was identified in the yaks (n = 11), Tibetan sheep (n = 1), and horses (n = 4). Three E. bieneusi genotypes, including a known genotype BEB4 and two novel ones SQY1 and SQY2, were identified in the yaks (n = 7), while in Tibetan sheep (n = 4) only the known genotype BEB4 was detected. The novel genotype SQY1 was grouped into the human-pathogenic Group 1, and the known genotype BEB4 and the novel genotype SQY2 were grouped into Group 2. Enterocytozoon bieneusi was not detected in horses. Conclusions Cryptosporidium suis was identified in yaks and horses while zoonotic E. bieneusi genotype BEB4 in Tibetan sheep for the first time, expanding their host ranges. These findings suggested that yaks, Tibetan sheep and horses could act as potential sources of human Cryptosporidium spp. and E. bieneusi infections, implying that the presence of zoonotic species/genotypes could pose a threat to public health.